Experimental and computational study of the mechanics of chikungunya - Matseke, Thabang Ofentse (Department of Human Biology, 2022)
Diseases outbreaks caused by infections from microorganisms like human immunodeficiency virus (HIV), influenza virus, Ebola virus, Zika virus, dengue virus, and malaria have infected millions of people in Africa. In Africa, viruses with a viral envelope, i.e. enveloped viruses, like HIV and influenza, cause thousands of deaths each year yet no cure exists. It has been proposed that the mechanical properties of enveloped viruses may play a role in viral entry into host cells. This dissertation aimed to study experimentally and computationally the mechanical properties of chikungunya virus to enable mechanobiological investigations of interactions between the chikungunya virus, and other enveloped viruses, and host cells involved in the infection process. The chikungunya virus strain used was the S27-African prototype and the virions underwent nanoindentation using atomic force microscopy (AFM). Tests were conducted in pH = 7.4 and 6.0 representing neutral extracellular and acidic endosomal environments, respectively, the latter promoting viral fusion. The height of the virion was recorded using AFM tapping mode before and after the indentation. The indentation tests were performed using AFM force spectroscopy mode. The spring constant of the virus was determined from the force-displacement data for an indentation force between 0.1 and 0.4 nN. The height and spring constant of the virions were considerably larger in the neutral extracellular environment (hᵥ = 57.8 ± 0.6 nm; kᵥ = 0.035 ± 0.003 N/m) than in the acidic endosomal environment (hᵥ = 46.0 ± 0.8 nm; kᵥ = 0.047 ± 0.003 N/m). It is proposed that the acidification of the environment caused partial or full dissociation of the glycoproteins from the membrane. Due to the hydrophobicity of the membrane and the way the glycoproteins are embedded, the membrane may also have dissociated from the capsid. A computational three-dimensional geometry of a chikungunya virus-like particle (VLP) was generated from cryogenic electron microscope (cryo-EM) images and developed into a finite element (FE) model to simulate nanoindentation tests. The VLP was represented as linear-elastic material. The calibration of the model using data from the indentation experiments in neutral extracellular environment predicted an elastic modulus of the chikungunya VLP of E = 2.9, 3.5 and 4.0 MPa for a Poisson's ratio of ᵥ = 0.4, 0.35 and 0.3, respectively. The experimental part of this dissertation provides new information on the mechanical properties of chikungunya virus and on possible mechanical and conformational changes of the virus during the infection process. The microstructural FE model, combined with the experimental data, can facilitate future studies into the mechanics and mechanobiology of virion-host cell interactions during infection.